S-Thiolation Targets Albumin in Heart Failure - Maura Brioschi; Erica Gianazza; Alice Mallia; Beatrice Zoanni; Alessandra Altomare; Alma Martinez Fernandez; Piergiuseppe Agostoni; Giancarlo Aldini; Cristina Banfi (Antioxidants, 2020)
Human serum albumin (HSA) is associated with several physiological functions, such as maintaining oncotic pressure and microvascular integrity, among others. It also represents the major and predominant antioxidant in plasma due to the presence of the Cys34 sulfhydryl group. In this study, we assessed qualitative and quantitative changes in HSA in patients with heart failure (HF) and their relationship with the severity of the disease. We detected by means of mass spectrometry a global decrease of the HSA content in the plasma of HF patients in respect to control subjects, a significant increase of thio-HSA with a concomitant decrease in the reduced form of albumin. Cysteine and, at a lesser extent, homocysteine represent the most abundant thiol bound to HSA. A strong inverse correlation was also observed between cysteine-HSA and peak VO2/kg, an index of oxygen consumption associated with HF severity. Moreover, in HL-1 cardiomyocytes incubated with H2O2, we showed a significant decrease of cell viability in cells treated with thio-HSA in respect to restored native-HSA. In conclusion, we found for the first time that S-thiolation of albumin is increased in the plasma of HF patients and induced changes in the structure and antioxidant function of HSA, likely contributing to HF progression.